Sagebrush rebel : Reagan's battle with environmental extremists and why it matters today - Pendley, William Perry, 1945- (Regnery Publishing, 2013)
The fascinating story of how Ronald Reagan, self-proclaimed "sagebrush rebel," took his revolutionary energy policies to Washington and revitalized the American economy.